Astrometrical Observations of the Selected WDS Stars - Bodryagin, D.V.; Bondarchuk, L.Ye.; Maigurova, N.V. (Science and Innovation, 2024)
The results of double stars observations, which were carried out at the Research Institute NAO during the 2013-2016 years are presented. Astrometric reduction of the received frames until the equatorial coordinates of binary and multiple systems components at the time of observation was made. The combination of the CCD received data with other Strasbourg base catalogs allowed to determine the new values of the observed stars’ proper motions. Parameters of mutual component configuration (position angle and separation) were measured for the 214 double stars. The analysis of the measurement results was carried out. The measurement results were added to the WDS directory database.